Writing Your First Primary Source Project: Lessons from TRIUMPHS Authorship Workshops - Clinkenbeard, Jennifer (Annals of the TRIUMPHS Society, 2026)
We provide a summary of the outcomes from the two Primary Source Project authorship workshops held by the TRIUMPHS Society in the fall of 2025.